Peer support and youth engagement - Ariffin, Zaifunizam; Krauss, Steven Eric; Abdullah, Haslinda; Ortega, Adriana; Ali, Zuraidah (Human Resource Management Academic Research Society, 2017)
This papers presents the preliminary results of a qualitative study on peers support and youth engagement. Data was obtained using in-depth interview; a total of 14 active and engaged youth shared their experience about how they got involved with and became engaged in youth organization programs and/or community work. The data elicited indicate peer their peers’ support and encouragement are important determinants in maintaining youth active and engaged in an organization or community programs. In addition, the preliminary results suggest that positive peer-based leadership program is the way forward to foster and maintain young people’s participation and engagement in youth organization and/or community based programs.